Complex approaches for education in Brazil - Patrícia Alessandra Morita Sakowski; Marina H. Tóvolli (Institute for Applied Economic Research (ipea), 2016)
Education systems can be viewed as complex systems, by considering that learning, teaching, cognition and education are phenomena resulting from interactions between the heterogeneous agents that compose such systems. Given the complex nature of education systems, new approaches seem relevant, and even necessary, if we consider that traditional methods are often not capable of capturing the dynamics of these systems. This paper aims to identify what has been done in Brazil regarding the complex system approach in education, and to bring to discussion the potential benefits of this perspective to education in the country. The main concepts that have marked the theoretical thought of complexity are presented, as well as applications of complex systems' methods and methodologies in education in Brazil, such as Agent-Based Modeling, Network Analysis, Intelligent Tutoring Systems, Educational Data Mining, and Learning Analytics, among others. Finally, some insights of the complex system approach to education are discussed.
Keywords: C53; C63; I21; I28; I24; 330; complex systems; education; complexity; agent-based models; network analysis; intelligent tutoring systems; educational data mining; learning analytics; public policies